Featured Cover - Burlot, Jacques; Vangu, Divine; Bellot‐Gurlet, Ludovic; Colomban, Philippe (Journal of Raman spectroscopy, 2024)
The cover image is based on the Special Issue – Research Article Raman identification of pigments and opacifiers: Interest and limitation of multivariate analysis by comparison with solid state spectroscopical approach—I. Lead‐tin and Naples Yellow by Jacques Burlot et al., https://doi.org/10.1002/jrs.6600.